Strategi Komunikasi Pemasaran Hibrid Aren Creativity dalam Pemberdayaan Pengrajin dan Perluasan Pasar Cobek Aren - Syalma Azzahra; Atwar Bajari; Ditha Prasanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the challenges faced by cobek aren craftsmen in Kampung Lamping, Ciamis Regency, in marketing their products after the pandemic. Aren Creativity emerged as a solution through the implementation of a hybrid marketing communication strategy that combines offline and online marketing methods. This study aims to explore how this strategy plays a role in empowering craftsmen and expanding the market for handicraft products. The research method used is descriptive qualitative with a case study approach. Data collection techniques were carried out through in-depth interviews and direct observation of business actors and local craftsmen. The findings show that the hybrid marketing communication strategy implemented by Aren Creativity successfully expanded the market reach of cobek aren products and encouraged the active involvement of craftsmen in the marketing chain. The combination of conventional and digital marketing has led to increased sales volume, strengthened local branding, and improved the welfare of the craftsmen. The research was analyzed using the Integrated Marketing Communication (IMC) theory by Don E. Schultz, which is relevant in describing message consistency and integration across communication channels. The implications of this study indicate that the hybrid marketing communication strategy is effectively applicable in the context of rural UMKM as an effort to empower communities and adapt to the digital era.